(untitled) (Revista Electrónica REDINE, 2022)
Entrepreneurship is a dynamic activity of society by providing economic and social benefits. Its study has multiple edges as well as theoretical and methodological orientations. For this reason, this study is presented, which seeks to generate contributions for the understanding of entrepreneurship from autoethnography. The latter, a qualitative method that allows providing a research product where the spatial and temporal context in which the study informants have lived their experience as entrepreneurs is understood, covering the cultural, social, economic and political dimensions. All this, to describe and understand their experiences from a conception of an interpretive nature. For data collection, an in-depth interview and participant observation were used. For the generation of categories, content analysis, reduction and integration of codes were used until the final categories were obtained. All this, a process that makes science and art concur in the same investigation. The latter, as a creative process together with the narrative with overtones of literary expression. The latter, as a creative process together with the narrative with overtones of literary expression. The final categories emerged from the testimonials and my interpretation: The entrepreneur and its essence, Entrepreneurship and its truth, and finally, Entrepreneurship and its consequences. With these categories I look for an organized whole that contributes to the understanding of the object of study.